KEABSAHAN PRAKTEK FASAKH DALAM PERKAWINAN KARENA MURTAD - Zainul Mu’ien Husni; Abdul Latief (Fakultas Agama Islam Universitas Nurul Jadid, 2022)
It is explained in the KHI that the apostasy of the husband or wife does not cause the marriage to be annulled if the parties concerned from the wife or husband do not take the case to the Religious Court. So that if one partner does not mind if his partner lapses, then the marriage can continue. KHI mentioned the reasons for divorce. It is stated that religious conversion or apostasy that causes disharmony in the household can be used as a reason for divorce. This provision is contrary to the Imam Madzhab. The results showed that there was a difference in the case of a husband and wife who apostatized in the middle of their marriage in their legal status. In the Syafi'i school, it was clear that the marriage was canceled. However, in the Compilation of Islamic Law, it is not very clear about the phase of marriage due to apostasy. The marriage broke up due to divorce due to the absence of household harmony, not due to apostasy committed by one of the parties (husband/wife). In the Compilation of Islamic Law, there should be an additional verse that one of the reasons for the annulment of a marriage is the apostasy of one of the husbands or wives. This addition is in line with the provisions of Islamic Law, where the majority of Islamic Ulama (Imam Madzhab) are very strict about the issue of the annulment of marriages due to apostasy. So that the Indonesian Muslim community, whose majority follows the Shafi'i Madzhab, has no confusion when dealing with regulations that are not by the provisions in force in Positive Law and Islamic Law.